Calibrating assessment literacy through benchmarking tasks. Issue 8 (17th November 2019) - Knight, Simon; Leigh, Andy; Davila, Yvonne C.; Martin, Leigh J.; Krix, Daniel W.
Abstract: In calibration tasks students assess exemplar texts using criteria against which their own work will be assessed. Typically, these tasks are used in the context of training for peer assessment. Little research has been conducted on the benefits of calibration tasks, such as benchmarking, as learning opportunities in their own right. This paper examines a dataset from a long-running benchmarking task (∼500 students per semester, for four semesters). We investigate the relationship of benchmarking performance to other student outcomes, including ability to self-assess accurately. We show that students who complete the benchmarking perform better, that there is a relationship between benchmarking performance and self-assessment performance, and that students appreciate the support for learning that benchmarking tasks provide. We discuss implications for teaching and learning flagging the potential of calibration tasks as an under-explored tool.